Deposit Guarantee Systems in Russia and the USA - Florczak, Tomasz; Paduszyńska, Marta (Journal of Finance and Financial Law, 2021)
The purpose of the article/hypothesis: The purpose of the article is to indicate the results of operations of deposit guarantee systems in Russia and the USA. The research hypothesis was that the deposit guarantee system in Russia during the 2004–2018 research period was more heavily burdened with guarantee activities.Methodology: The article is largely based on a review, analysis and synthesis of selected publications and available statistical data. Additionally, it is expanded by the authors’ conclusions and the results of their research.Results of the research: They clearly indicate a high burden on the institution guaranteeing deposits in Russia (DIS). This is primarily the result of actions aimed at stabilizing the Russian banking sector.